2009
DOI: 10.4103/0378-6323.45218
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of early onset psoriasis in comparison with late onset psoriasis: A clinical study from Pakistan

Abstract: Patients with early and late onset psoriasis in Pakistani population do not show different clinical and demographic features contrary to the Western patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
24
5
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 0 publications
10
24
5
3
Order By: Relevance
“…[12] We found that 22% of patients have a family history of psoriasis which is similar to study carried out by Ejaz et al . [13] However, Raychaudhuri and Farber found that 54% of the adults had a positive prevalence of family history which is higher than our study. [14] This difference is due to patients may unaware about their parent's disease status or may be due to different genetic basis.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…[12] We found that 22% of patients have a family history of psoriasis which is similar to study carried out by Ejaz et al . [13] However, Raychaudhuri and Farber found that 54% of the adults had a positive prevalence of family history which is higher than our study. [14] This difference is due to patients may unaware about their parent's disease status or may be due to different genetic basis.…”
Section: Discussioncontrasting
confidence: 83%
“…[14] This difference is due to patients may unaware about their parent's disease status or may be due to different genetic basis. [13]…”
Section: Discussionmentioning
confidence: 99%
“…There are few data about epidemiological, clinical and genetic aspects of childhood psoriasis. Main characteristics are a higher frequency of napkin and guttate psoriasis, and a higher genetic background . Little information is available about psoriasis in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrodermic psoriasis has a higher prevalence in those patients, whereas the scalp skin of the elderly patients with plaque psoriasis is more frequently affected. On the contrary, younger patients usually present with erythematosquamous plaques on the knees and elbows [153,[166][167][168].…”
Section: Immunologic Diseasesmentioning
confidence: 99%